Posterior capsule opacification treatment using Nd: YAG laser capsulotomy: 36 months retrospective analysis - Andrius Montrimas; Jorė Rinkevičiūtė; Reda Žemaitienė (BMC Ophthalmology)
Abstract Background The study aimed to identify factors influencing the time from cataract surgery to PCO treatment with Neodymium: Yttrium-Aluminium-Garnet (Nd: YAG) laser. Methods For PCO risk factors analysis the retrospective study included 1045 eyes treated for PCO using Nd: YAG laser capsulotomy in the Hospital of Lithuanian University of Health Sciences (HLUHS) Kaunas Clinics with reduced best-corrected distance visual acuity (BCDVA) and opacity in the central 3 mm zone. Eyes with no comorbidities were categorized into groups according to the intraocular lense (IOL) implanted and the time from cataract operation to Nd: YAG capsulotomy was compared. Tests used for statistical analysis: Shapiro-Wilk, Kruskal-Wallis, Mann-Whitney, one-way independent ANOVA, Pearson’s or Spearman’s correlation coefficient, and multivariable linear regression. Results A total of 918 patients (1045 eyes) were included. The median time from cataract surgery to capsulotomy was 39.0 (27.4–54.6) months (min. 2; max. 174), did not differ between men and women, and was shorter for junior surgeons (25.8 (19.8–35.1) months) compared to senior surgeons (39.6 (27.8–55.3) months) (p < 0.001). Seven factors affecting the time from cataract surgery to Nd: YAG capsulotomy were found: IOL model, surgeon’s experience, BCDVA after surgery, capsular tension ring, pseudoexfoliation, BCDVA before capsulotomy and exudative age-related macular degeneration (adjusted R2 = 0.452; p < 0.001). The IOL model was the only factor with a strong correlation. The median time from cataract surgery to capsulotomy differed between all IOL groups: Acriva UD613 group 31.5 (23.0–38.0) months, Johnson&Johnson Tecnis ZCB00 group 41.0 (33.5–66.5) months, Bausch&Lomb Envista MX60 group 45.0 (38.5–54.5) months, and Alcon Acrysof IQ SN60WF group 53.0 (41.5–79.5) months. Conclusions The IOL model seems to have the greatest influence on the time from cataract surgery to Nd: YAG capsulotomy. Acrylic hydrophobic IOLs with a square optical edge have different times from cataract surgery to Nd: YAG capsulotomy. Hydrophobic acrylic IOL seems to have a longer time from cataract surgery to Nd: YAG capsulotomy compared to hydrophilic acrylic IOL with a hydrophobic surface.